2020
DOI: 10.1007/s10010-019-00390-1
|View full text |Cite|
|
Sign up to set email alerts
|

Efficiency and heat balance calculation of worm gears

Abstract: Worm gears enable compact gear design and high power density due to a high gear ratio within a single gear stage. However, they often show high sliding speeds within the tooth contact, resulting in high frictional heat and increased thermal stresses. Therefore, an exact calculation regarding efficiency and heat balance is essential in the early stages of gear design. Currently, no calculation method is available to automatically analyze worm gears with regard to efficiency and heat balance. The simulation prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…The rolling elements transport heat out of the contact and contribute based on the heat fluxes to the surrounding system to its inner temperature distribution. To describe the heat balance of gearboxes, a thermal network can be established (Paschold et al , 2020). By abstraction of the gearbox system by nodal points, an efficient calculation of heat transfer, dissipation and generation is set up.…”
Section: On the Thermal Insulation Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The rolling elements transport heat out of the contact and contribute based on the heat fluxes to the surrounding system to its inner temperature distribution. To describe the heat balance of gearboxes, a thermal network can be established (Paschold et al , 2020). By abstraction of the gearbox system by nodal points, an efficient calculation of heat transfer, dissipation and generation is set up.…”
Section: On the Thermal Insulation Effectmentioning
confidence: 99%
“…Micro thermal networks for TEHL contacts may be implemented in thermal network models of gearboxes, such as described in (Paschold et al , 2020). Based on the interaction between the micro thermal network and the surrounding system, a bulk temperature of the rolling elements adjusts.…”
Section: On the Thermal Insulation Effectmentioning
confidence: 99%
“…The wheel bulk temperature can, for example, be calculated with DIN 3996 [2]. As it depends strongly on the heat dissipation properties of the gear box system [27,28], the wheel bulk temperature might also be measured on the actual gear box for better accuracy. The flash temperature is determined with Eq.…”
Section: Derived Formulas For Contact Temperature Calculationmentioning
confidence: 99%
“…In this study, the TNM in WTplus as shown by the authors in [32] is extended to calculate gearbox component temperatures for transient operation conditions.…”
Section: Introductionmentioning
confidence: 99%